2016
DOI: 10.1007/s00192-016-3000-1
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of vaginal estrogen on pessary use

Abstract: Introduction and hypothesis Many providers recommend concurrent estrogen therapy with pessary use to limit complications; however, limited data exist to support this practice. We hypothesized that vaginal estrogen supplementation decreases incidence of pessary-related complications and discontinuation. Methods We performed a retrospective cohort study of women who underwent a pessary fitting from 1 January 2007 through 1 September 2013 at one institution; participants were identified by billing code and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…However, recent small, nonrandomized studies have reported no clear benefit in reduction of discomfort with pessary removal or ulceration and bleeding when women elect to use vaginal estrogen, thus reinforcing the need for further study . One self‐selected group of women who chose to use vaginal estrogen did exhibit a higher incidence of continued pessary use and lower incidence of increased vaginal discharge than women who did not …”
Section: Discussionmentioning
confidence: 99%
“…However, recent small, nonrandomized studies have reported no clear benefit in reduction of discomfort with pessary removal or ulceration and bleeding when women elect to use vaginal estrogen, thus reinforcing the need for further study . One self‐selected group of women who chose to use vaginal estrogen did exhibit a higher incidence of continued pessary use and lower incidence of increased vaginal discharge than women who did not …”
Section: Discussionmentioning
confidence: 99%
“…72 A retrospective cohort study of 134 women treated with pessaries for at least 3 months demonstrated that women using vaginal estrogen were more likely to continue pessary use. 73 While topical estrogen did not impact the rate of vaginal ulcerations and related vaginal bleeding, women who used vaginal estrogen were less likely to experience bothersome vaginal discharge compared with those who did not. 73…”
Section: Decline In Estrogen and Pelvic Organ Prolapsementioning
confidence: 92%
“…73 While topical estrogen did not impact the rate of vaginal ulcerations and related vaginal bleeding, women who used vaginal estrogen were less likely to experience bothersome vaginal discharge compared with those who did not. 73…”
Section: Decline In Estrogen and Pelvic Organ Prolapsementioning
confidence: 92%
“…Seven studies provided data on risk of adverse events with long-term pessary use (without removal or cleaning) [17][18][19][20][21][22][23]. Nine additional articles were reviewed that provided information of interest during the pandemic [24][25][26][27][28][29][30][31][32]. Our analysis included three randomized controlled trials, three prospective cohorts, and one retrospective cohort.…”
Section: Pessary Managementmentioning
confidence: 99%
“…Use of a specific telemedicine encounter is preferred for tracking and reimbursement purposes over a telephone encounter (typically used for sharing of discrete information) & Patients can safely extend the time interval between pessary cleanings to 6 months (and, in some cases, up to 24 months) with minimal risk of adverse events [17][18][19][20][21][22][23]. & Patients capable of pessary removal and reinsertion should be encouraged to self-clean their pessary [27,[31][32][33][34][35]. & Providers should consider empiric vaginal estrogen to minimize adverse events for patients not already using vaginal estrogen [17,18,28,31,33].…”
Section: Pessary Managementmentioning
confidence: 99%